Study of Reliable Design Using T-S Fuzzy Modeling and Integral Sliding Mode Control Schemes - Liang, Yew-Wen; Chen, Chih-Chiang; Xu, Sendren Sheng-Dong (My University, 2013)
This paper investigates robust active reliable control issues using a combination of Takagi-Sugeno (T-S) fuzzy system modeling and Integral Sliding Mode Control (ISMC) schemes. The presented reliable scheme is shown to retain the benefits of both T-S modeling and ISMC design. It not only alleviates the online computational burden due to the use of the T-S model but also preserves the many advantages of the ISMC scheme. Using the presented reliable scheme, the control mission can be successfully achieved without prompt external support even when some of the actuators fail to operate. Moreover, because the ISMC design allows the engineer to predict the performance of the uncertain system from that of the nominal control system, the presented reliable scheme also possesses a degree of freedom in the design of the nominal controller for better system performance of normally operated and different faulty, uncertain situations. An illustrative example is also given to demonstrate the benefits of the proposed scheme.
Keywords: Takagi-Sugeno fuzzy models; Reliable control; Integral sliding mode control; Nonlinear systems; Sliding mode control